Increased Phosphate Level in Peat Soil Media Given Formulation Biofertilizer Dosage - Gea, Noveria; Hasibuan, Saberina; Syafriadiman, Syafriadiman (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT                This research was conducted on May 1st to July 31th, 2018, on Peatlands, Kualu Nenas Village, Tambang District, Kampar District, Riau Province. Sample analysis was carried out at the Laboratory of Aquaculture Quality and Fisheries Technology, Faculty of Fisheries and Marine, University of Riau. The method used in this study is an experimental method using a Complete Random Design (CRD) with 1 factor, 5 treatments and 4 replications.. The treatments in this study were P0 (control), P1 (300 g/m2), P2 (450 g/m2), P3 (600 g/m2) and P4 (750 g/m2). The container is used by 20 barrel units made of PVC with a diameter of 59 cm and a height of 100 cm with an area of 273 cm2 (0.273 m2). The results of the research that has been done show that there is an effect of dosing biofertilizer on phosphate changes in peat soil.The best dose of biofertilizer in this study was found in P4 (750 g/m2) with a P level of Total 1.07% and phosphate levels in water 3.91 mg/l. The linear regression test between P Total (%) and the formulation biofertilizer dose is y = 0.0629 + 0.0013x, the contribution value is R2 = 0.95. The increase in total P concentration was influenced by biofertilizer doses of 95.01% and influenced by 4.99% by other factors. The coefficient of determination of the correlation (r) is 0.97 means that there is a very strong positive relationship between the total P concentration with the biofertilizer dose; Linear regersi test between Phosphate water (mg / l) and formulation biofertilizer dosage is y = 1.9974 + 0.0021x, the contribution value is R2 = 0.79. Increased phosphate water concentration was influenced by biofertilizer doses of 79.16% and influenced by 20.84% by other factors. The coefficient of determination of the correlation (r) is 0.88 means that there is a very strong positive relationship between the phosphate concentration of water and the dose of biofertilizer. Water quality parameters during the study included temperature ranging from 26-32 0C, pH ranged from 6-7, DO ranged from 3.2 to 8.6, CO2 from 13.31 to 49.94 mg/l, and turbidity values ranged from 18 -21.25 NTU.Keyword: Phosphate, Biofertilizer, Peat soil